Effects of Political Governance and Public Health Intervention on Food Security Among Small Scale Farmers in Adamawa North - Wazakari, Rogers Roland; Reuben, Biyama Chama; Gambo, Momsiri Wesley (Kashere Journal of Politics and International Relations, 2025)
The study assesses the impact of political governance and public health intervention on food security among small scale farmers in Adamawa North. The issue of food security has been a central concern for many decades. Food security is achieved when all individuals have consistent physical, government policy and economic access to sufficient, safe, and nutritious food that meets their dietary needs and preferences for an active and healthy life. The main objective of the study is to assess the impact of political governance and public health intervention on food security among small scale farmers in Adamawa North while the specific objectives are to describe the socio-economic characteristics of small-scale farmers in the study area and to identify the determinants of food security among the respondents in the study area. The study reviews related literature on good governance, public health intervention and food security while system theory is adopted as the theoretical framework. The main source of data for this study is primary. The study used inferential statistics such as frequency distribution and percentage for the socio-economic characteristics of the respondents and logit regression is used on the determinant of food security. The study discovered that there are no target programmes and policies to improve food production in Adamawa North. The study recommends that there should be targeted programs to provide small scale farmers with access to essential agricultural inputs such as seeds, fertilizers, and farming equipment.